Materia i forma sakramentu Eucharystii - Janczewski, Zbigniew (Prawo Kanoniczne, 2005)
Jesus Christ constituted the sacrament of Eucharist during last supper. This article shows what it is the matter and the form of this sacrament. It quotes the bibical texts from the New Testament and the writings of the Fathers of the Church. It analyses the law of Holy See: the Popes, the Councils, and the Vatican Congregations. At the beginning the article shows the matter which is necessary to consecration of the bread, and to consecration of the wine. This bread and this wine will becoming later the Blood and the Body of Jesus Christ. The next part of this article is about the form conforming to Eucharist. The last part of this elaboration shows, what influence have the different defects of the matter and the form, relating on validity of consecration of Eucharist.